Supporting Learning Differences: Effects of Cognitive Training on Cognitive Abilities in a School-Based Sample - Lisa Looney; Eugene H. Wong; Kevin P. Rosales; Jennifer M. Bacon; Dudley J. Wiest (MDPI AG, 2024)
A growing body of research demonstrates the effectiveness of computerized cognitive training (CCT) in building specific abilities (e.g., working memory) among school-age children. As a result, CCT is increasingly cited as a means to enhance and support students' academic performance and school experience. However, many studies exploring CCT as an intervention have done so outside of the school setting, limiting its potential impact with regard to students who may benefit from it but cannot access such supports. This project examined the efficacy of a CCT program implemented within the academic day for all students attending a private school. The findings showed that two CCT programs resulted in improvements in working memory, cognitive flexibility, and/or processing speed among third graders through sixth graders (N = 95). Furthermore, this project demonstrates a model for the effective integration of CCT into a school day without interrupting the academic curriculum. The present results have important implications for the current ideological shift in education that focuses on how to more broadly address students' learning differences.